Coding-Based AR Puzzle Media to Improve Mutual Cooperation and Computational Thinking in Elementary School Students - Ni Made Ayu Liyoga Sari; I Kadek Suartama; Ni Made Daini Vitri Sinta Sari (Thinking Skills and Creativity Journal, 2025)
The limited development of students’ collaboration attitudes as part of the Pancasila Student Profile and insufficient computational thinking skills remain major challenges in elementary science and social studies (IPAS) learning. These challenges are exacerbated by the suboptimal use of interactive and technology-integrated learning media. This study aims to develop, validate, analyze user responses to, and examine the effectiveness of a coding-based augmented reality (AR) puzzle medium in enhancing students’ collaboration attitudes and computational thinking skills. This research employed a research and development design using the ADDIE model and involved 30 elementary school students as research participants. Data were collected through interviews, observations, and questionnaires, supported by expert validation sheets, student response questionnaires, computational thinking tests, and collaboration attitude observation rubrics. Data were analyzed using quantitative and qualitative techniques, with content validity assessed through the Content Validity Index (CVI), descriptive statistics used to analyze student responses, and a paired sample t-test applied to examine the effectiveness of the developed media. The findings indicate that the coding-based AR puzzle medium demonstrates high validity, receives very positive responses from students, and is conceptually effective in strengthening collaboration attitudes and improving computational thinking skills in IPAS learning. It can be concluded that the developed medium has strong potential as an innovative learning resource to foster exploratory, contextual, and interactive learning experiences while supporting meaningful technology integration in elementary education.